Membrane-Based Separation of Phenol/Water Mixtures Using Ionically and Covalently Cross-Linked Ethylene-Methacrylic Acid Copolymers - Alexander Mixa; Claudia Staudt (International Journal of Chemical Engineering)
Membrane-based separation of phenol/water mixtures with concentrations of phenol between 3 wt% and 8 wt% in the feed has been performed with nonmodified as well as cross-linked ethylene-methacrylic acid (E-MAA) copolymers with different amounts of methacrylic acid. As cross-linking agents, aluminium acetyl acetonate, which leads to ionically cross-linked membranes, and 2,3,5,6-tetramethyl-1,4-phenylene diamine and glycerine digycidether, leading to covalently cross-linked membranes, have been used. Generally, it was found that with increasing phenol content in the feed, the total flux is increasing whereas the enrichment factor is decreasing. Using nonmodified membranes with higher methacrylic acid monomer content in the polymer, lower fluxes and higher enrichment factors were observed. Investigation of different cross-linked membranes showed that with high phenol concentration in the feed, ionic cross-linking seems to be very promising. Furthermore, variation of feed temperature shows that ionically cross-linked membranes reached higher fluxes as well as higher enrichment factors at elevated temperatures. The temperature-dependent data were fitted based on an Arrhenius-type equation, and activation energies for the permeation of phenol and water through the membrane were calculated.